A study on patients’ perception of the quality of private medical college hospitals in Thrissur District, Kerala - .K, Antony.T; Ramadevi, V. (International Journal of Psychosocial Rehabilitation, 2020)
Programs on health management and institutional healthcare are two important aspects of healthcare system. The institutions offer highly innovative and cost-effective treatment. The researcher designed the study to estimate the patient perception with regard to diagnosis, advise on medication, service availability,lapse of time,the behaviour of doctors and expenses in privatemedical college hospitals’ outpatient departments..The perception of patients on quality of health facilities are normally high. The doctors’ approach has good influence on the satisfaction of patientwith regard toinfrastructure of hospitals, behavior of other staffs and the availability of medical information. The response of in-patientstake into consideration the behavior of staff,thedoctors’ approach and behavior, medicines prescribed, medical details and infrastructure of hospital.In the study the researcher tries to identify the variables that influence the perception of patients on the services of private medical college hospitals inThrissur District.